Acceptability of intermittent preventive treatment of malaria in pregnancy with sulfadoxine-pyrimethamine plus dihydroartemisinin-piperaquine in Papua New Guinea: a qualitative study - Elvin Lufele; Sophie Pascoe; Alice Mengi; Alma Auwun; Nalisa Neuendorf; John W. Bolnga; Moses Laman; Stephen J. Rogerson; Kamala Thriemer; Holger W. Unger (Malaria Journal)
Abstract Background In moderate-to-high malaria transmission regions, the World Health Organization recommends intermittent preventive treatment in pregnancy (IPTp) with sulfadoxine-pyrimethamine (SP) alongside insecticide-treated bed nets to reduce the adverse consequences of pregnancy-associated malaria. Due to high-grade Plasmodium falciparum resistance to SP, novel treatment regimens need to be evaluated for IPTp, but these increase pill burden and treatment days. The present qualitative study assessed the acceptability of IPTp-SP plus dihydroartemisinin-piperaquine (DP) in Papua New Guinea, where IPTp-SP was implemented in 2009. Methods Individual in-depth interviews (IDIs) and focus group discussions were conducted at health facilities where a clinical trial evaluated IPTp-SP plus DP (three-day regimen) versus IPTp-SP plus DP-placebo. IDIs were conducted with: (1) trial participants at different stages of engagement with ANC and IPTp, e.g. first antenatal clinic visit, subsequent antenatal clinic visits and postpartum; (2) local health workers (nurses, community health workers, midwives, health extension officers, doctors); and (3) representatives of district, provincial and national health authorities involved in programming ANC and IPTp. Focus group discussions comprised pregnant women only, including those engaged in the clinical trial and those receiving routine ANC outside of the trial. All interviews were audio recorded and transcribed. Transcripts were analysed using inductive and deductive thematic analysis applying a framework assessing: affective attitude, burden, ethicality, intervention coherence, opportunity costs, perceived effectiveness, and self-efficacy. Results Women expressed positive feelings and attitudes towards SP plus DP/DP-placebo; reported limited side effects; and found the size, number, colour, and taste of study medicines acceptable. Health workers and policymakers were concerned that, compared to SP alone, additional tablets, frequency (three-day regimen), and tablet size might be barriers to acceptability for users outside a non-trial setting. There was a high perceived effectiveness of SP plus DP; most women reported that they did not get malaria or felt sick during pregnancy. Broader healthcare benefits received through trial participation and the involvement of health workers, relatives and community members in the clinical trial enabled antenatal clinic attendance and perceived acceptability of this IPTp regimen. Conclusions In the trial context, IPTp-SP plus DP was acceptable to both users and providers. Healthcare providers were concerned about the realities of acceptability and adherence to SP plus DP outside a clinical trial setting.